The Psoriatic Arthritis Impact of Disease 12-item questionnaire: equivalence, reliability, validity, and feasibility of the touch-screen administration versus the paper-and-pencil version - Salaffi F; Di Carlo M; Carotti M; Farah S; Gutierrez M (Dove Medical Press, 2016)
Fausto Salaffi,1 Marco Di Carlo,1 Marina Carotti,2 Sonia Farah,3 Marwin Gutierrez1,4 1Rheumatology Department, Polytechnic University of Marche, 2Radiology Department, Polytechnic University of Marche, 3DII, Department of Information Engineering, Polytechnic University of Marche, Ancona, Italy; 4Musculoskeletal Department, National Rehabilitation Institute, Mexico City, Mexico Background: Over the last few years, there has been a shift toward a more patient-centered perspective of the disease by adopting patient-reported outcomes. Touch-screen formats are increasingly being used for data collection in routine care and research. Objectives: The aim of this study is to examine the equivalence, reliability, validity and respondent preference for a computerized touch-screen version of the Psoriatic Arthritis Impact of Disease 12-item (PsAID-12) questionnaire in comparison with the original paper-and-pencil version, in a cohort of patients with psoriatic arthritis (PsA). Methods: One hundred and fifty-nine patients with PsA completed both the touch screen- and the conventional paper-and-pencil administered PsAID-12 questionnaire. Agreement between formats was assessed by intraclass correlation coefficients. Spearman’s rho correlation coefficient was used to test convergent validity of the touch screen format of PsAID-12, while receiver operating characteristic curve analysis was performed to test discriminant validity. In order to assess the patient’s preference, the participants filled in an additional questionnaire. The time taken to complete both formats was measured. Results: A high concordance between the responses to the two modes of the PsAID-12 tested was found, with no significant mean differences. Intraclass correlation coefficients between data obtained for touch-screen and paper versions ranged from 0.801 to 0.962. There was a very high degree of correlation between the touch-screen format of PsAID-12 and composite disease activity indices (all at a P level <0.0001), Health Assessment Questionnaire, and Physician Assessment of disease activity. The discriminatory power of the touch-screen format of PsAID-12, assessed using the minimal disease activity – Outcome Measurements in Rheumatology Clinical Trials criteria, was very good, with an area under the receiver operating characteristic curve of 0.937 and a resulting cutoff value of 2.5. The touch-screen questionnaire was readily accepted and preferred. The mean time spent for completing the questionnaire on touch screen was 2 minutes and on paper was 2.7 minutes. Conclusion: The touch-screen mode of administration of PsAID-12 can be a feasible and suitable alternative to the paper-and-pencil mode for the assessment of patients with PsA. Keywords: psoriatic arthritis, PsAID-12, touch-screen questionnaire, patient-reported outcomes